Resistance of Klebsiella pneumoniae Strains Carrying blaNDM–1 Gene and the Genetic Environment of blaNDM–1 - Xiang, Tianxin; Chen, Chuanhui; Wen, Jiangxiong; Liu, Yang; Zhang, Qi; Cheng, Na; Wu, Xiaoping; Zhang, Wei (Frontiers in Microbiology, 2020)
Objective Regional dissemination is the major cause of the widespread prevalence of a plasmid-encoding NDM-1 enzyme. We investigated the drug resistance, joint efficiency, and gene environment of a Klebsiella pneumoniae strain carrying blaNDM–1 gene. Materials and Methods Carbapenem-non-susceptible strains were analyzed using the VITEK 2 Compact. Strains carrying blaNDM–1 were identified using polymerase chain reaction and sequencing. Antimicrobial susceptibility testing and plasmid conjugation experiments were then conducted. Strains carrying blaNDM–1 were subjected to Southern blot analysis. After the gene mapping of blaNDM–1, library construction, and sequencing, plasmids were subsequently spliced and genotyped using the software Glimmer 3.0, and then analyzed using Mauve software. Results Among 1735 carbapenem-non-susceptible strains, 54 strains of blaNDM–1-positive bacteria were identified, which consisted of 44 strains of K. pneumoniae, 8 strains of Acinetobacter baumannii and 2 strains of Escherichia coli. Strains carrying blaNDM–1 had a resistance rate of more than 50% in most antibiotics. Plasmid conjugation between strains carrying blaNDM–1 and E. coli strain J53 had a success rate of 50%. Southern blot analysis indicated that each strain had multiple plasmids containing blaNDM–1. Among the five plasmids containing blaNDM–1 in K. pneumoniae for sequencing, two plasmids with complete sequences were obtained. The findings were as follows: (i) The p11106 and p12 plasmids were highly similar to pNDM-BTR; (ii) the p11106 and p12 plasmids showed differences in the 20–30 kb region (orf00032–orf00043) from the other six plasmids; and (iii) blaNDM–1 was located at orf00037, while ble was found at orf00038. Two tnpA genes were located in the upstream region, and orf00052 (tnpA) in the 36 kb region was in the downstream sequence. Conclusion blaNDM–1-containing bacteria exhibit multidrug resistance, which rapidly spreads and is transferred through efficient plasmid conjugation; the multidrug resistance of these bacteria may be determined by analyzing their drug-resistant plasmids. The presence of ble and tnpA genes suggests a possible hypothesis that blaNDM–1 originates from A. baumannii, which is retained in K. pneumoniae over a long period by transposition of mobile elements.